Maximizing the success of resource parents who care for adolescents: training recommendations from caregivers and child welfare professionals. Issue 3 (26th May 2020) - Patterson, Debra; Day, Angelique; Vanderwill, Lori; Willis, Tamarie; Stevens, Kim; Simon, June; Cohick, Sue; Henneman, Kris
ABSTRACT: This study is one component of a larger project to design and evaluate a 12-hour national, in-service training curriculum for resource parents of adolescents who have experienced trauma. To inform curriculum development, this study explored perspectives and recommendations of resource parents and child welfare professionals on how trainings may adequately prepare resource parents for this role. Two major themes were identified. Participants believed that trainings need to be relatively more interactive than didactic to increase opportunities to develop skill and affective competencies (e.g., self-awareness). Participants also reported that trainings should include parent and adolescent trainers, who could provide a realistic understanding of resource parent struggles and successes.